NON-INVASIVE ASSESSMENT OF CENTRAL AORTIC PRESSURE, AORTIC FLOW AND VASCULAR LOAD IN PATIENTS WITH AORTIC STENOSIS BEFORE AND AFTER TRANSCATHETER AORTIC VALVE REPLACEMENT. (April 2021) - Adji, Audrey; Song, Ning; Hungerford, Sara; Namasivayam, Mayooran; Hayward, Christopher; Jabbour, Andrew; Muller, David
Abstract : Objective: The left ventricle (LV) faces a dual afterload in patients with aortic stenosis (AS), both from the narrowed valve and age-related arterial stiffening. Variability in indices of AS severity assessment suggests an inter-relationship of the valvular pressure gradient on systemic arterial pressure and flow. Our study aims to evaluate the dynamic vascular load (VL) non-invasively in AS patients before and after transcatheter aortic valve replacement (TAVR) using the approach of simultaneous cardiac magnetic resonance (CMR) and radial applanation tonometry (AT). Design and method: Ascending aortic pressure, flow and VL were measured in 3 patients at baseline and post-TAVR using a previously reported simultaneous CMR/AT technique. CMR provided aortic flow, and radial AT waves were converted offline to aortic pressure using SphygmoCor 8.1 (AtCor Medical) and calibrated using brachial cuff values. VL was determined as the relationship of derived aortic pressure to CMR aortic flow velocity, by calculating the average modulus of pressure divided by flow. Following the acquisition of post TAVR data, 300 micrograms of sublingual nitroglycerine (GTN) was introduced to investigate the effect on changing vascular load. Results: At 38 ± 3 days post TAVR, mean aortic pressure (MP) and mean systolic flow (MF) both increased (100 ± 17 pre, 109 ± 12 post, mmHg; 178 ± 44 pre, 230 ± 74 post, ml/s). Following GTN administration, MP (95 ± 3 mmHg) decreased but not MF (228 ± 57 ml/s) – see figure. Figure. No caption available. The steady state systemic vascular resistance (SVR) reduced post TAVR (22501 ± 5929 pre, 20484 ± 6232 post, dynes.s/cm3), but not VL (1082 ± 219 pre, 1111 ± 483 post, dynes.s/cm3). Conversely, GTN administration significantly reduced VL (838 ± 295 dynes.s/cm3) with little effect on SVR (19313 ± 5631 dynes.s/cm3). Conclusions: Our study demonstrates that our novel technique can be reliably replicated in patients to evaluate the changes to aortic pressure, flow and VL before and after TAVR. VL appears to be a dynamic measurement of vascular stiffness independent of AS and may prove to be a useful measure to predict haemodynamic responses and ventriculo-arterial coupling in AS patients post TAVR. Larger longitudinal cohort studies are warranted.